Association of amino acids and parameters of bone metabolism with endothelial dysfunction and vasculopathic changes in limited systemic sclerosis - Jud, Philipp; Meinitzer, Andreas; Strohmaier, Heimo; Arefnia, Behrouz; Wimmer, Gernot; Obermayer-Pietsch, Barbara; Foris, Vasile; Kovacs, Gabor; Odler, Balazs; Moazedi-Fürst, Florentine; Brodmann, Marianne; Hafner, Franz (Frontiers in Medicine, 2023)
Objectives Pathways contributing to endothelial dysfunction in patients with limited cutaneous systemic sclerosis (lcSSc) are largely unknown. The aim of this study was to investigate potential associations of amino acids and parameters of bone metabolism with endothelial dysfunction and vasculopathy-related changes in patients with lcSSc and early-stage vasculopathy. Methods Amino acids, calciotropic parameters, including 25-hydroxyvitamin D and parathyroid hormone (PTH), and bone turnover parameters, including osteocalcin and N-terminal peptide of procollagen-3 (P3NP), were measured in 38 lcSSc patients and 38 controls. Endothelial dysfunction was assessed by biochemical parameters, pulse-wave analysis, flow-mediated and nitroglycerine-mediated dilation. Additionally, vasculopathy-related and SSc-specific clinical changes including capillaroscopic, skin, renal, pulmonary, gastrointestinal and periodontal parameters were recorded. Results No significant differences in amino acids, calciotropic and bone turnover parameters were observed between lcSSc patients and controls. In patients with lcSSc, several significant correlations were found between selected amino acids, parameters of endothelial dysfunction, vasculopathy-related and SSc-specific clinical changes (all with p < 0.05). In addition, significant correlations were observed between PTH and 25-hydroxyvitamin D with homoarginine, and between osteocalcin, PTH and P3NP with modified Rodnan skin score and selected periodontal parameters (all with p < 0.05). Vitamin D deficiency defined as 25-hydroxyvitamin D < 20 ng/ml was associated with the presence of puffy finger (p = 0.046) and early pattern (p = 0.040). Conclusion Selected amino acids may affect endothelial function and may be associated to vasculopathy-related and clinical changes in lcSSc patients, while the association with parameters of bone metabolism seems to be minor.